Esophageal balloon dilation in children: prospective analysis of hemodynamic changes and complications during general anesthesia - KIYAN, GÜRSU (ELSEVIER SCIENCE INC, 2007)
Study Objective: To investigate hemodynamic changes and complications in children during balloon dilation of esophageal strictures. Design: Prospective, controlled study. Setting: University teaching hospital. Patients: 5 ASA physical status I and II pediatric patients with benign esophageal stricture related to ingestion of caustic substances. Interventions: Anesthesia was induced with intravenous propofol two mg/kg and cisatracurium 0.2 mg/kg and maintained with 66% nitrous oxide and one minimum alveolar concentration of sevoflurane in oxygen. In each session, balloon size was increased until the stricture was opened. Measurements and Results: A total of 18 sessions and 99 dilations in 5 children performed over a one-year period were included in the study. In 8 of 18 sessions, esophageal stricture was located in the middle one third of the esophagus; and in the others, in the upper one third. Four cases experienced bleeding; two cases, inability to ventilate due to obstruction of the endotracheal tube tip by the inflated balloon; and two cases, postextubation bronchospasm. In 95 of the 99 dilations, while the balloon was inflated, heart rate was faster and blood pressure increased significantly. Conclusion: Anesthesiologists should keep in mind the possibility of hemodynamic instability and possible endotracheal tube tip obstruction by the inflated balloon and safeguard the airway against bleeding, secretions, and radio-opaque fluid during esophageal balloon dilation. (c) 2007 Elsevier Inc. All tights reserved.
Keywords: balloon dilation; caustic ingestion; children; esophageal stricture; general anesthesia; MUSCLE-ACTIVITY; DISTENSION; DIAPHRAGM; RESPONSES